A Census of Dwarf Galaxy Satellites around LMC-mass Galaxy NGC 2403 - Jeffrey L. Carlin; David J. Sand; Burçin Mutlu-Pakdil; Denija Crnojević; Amandine Doliva-Dolinsky; Christopher T. Garling; Annika H. G. Peter; Jean P. Brodie; Duncan A. Forbes; Jonathan R. Hargis; Aaron J. Romanowsky; Kristine Spekkens; et al. (The Astrophysical Journal)
We present the first comprehensive census of the satellite population around a Large Magellanic Cloud stellar-mass galaxy, as part of the Magellanic Analog Dwarf Companions and Stellar Halos (MADCASH) survey. We have surveyed NGC 2403 ( D = 3.0 Mpc) with the Subaru/Hyper Suprime-Cam imager out to a projected radius of 90 kpc (with partial coverage extending out to ∼110 kpc, or ∼80% of the virial radius of NGC 2403), resolving stars in the uppermost ∼2.5 mag of its red giant branch. By looking for stellar overdensities in the red giant branch spatial density map, we identify 149 satellite candidates, of which only the previously discovered MADCASH J074238+65201-dw is a bona fide dwarf, together with the more massive and disrupting satellite DDO 44. We carefully assess the completeness of our search via injection of artificial dwarf galaxies into the images, finding that we are reliably sensitive to candidates down to M _V ∼ −7.5 mag (and somewhat sensitive to even fainter satellites). A comparison of the satellite luminosity function of NGC 2403 down to this magnitude limit to theoretical expectations shows overall good agreement. This is the first of a full sample of 11 Magellanic Cloud–mass host galaxies we will analyze, creating a statistical sample that will provide the first quantitative constraints on hierarchical models of galaxy formation around low-mass hosts.